HUBUNGAN PENDIDIKAN AGAMA ISLAM TERHADAP ETIKA PESERTA DIDIK KELAS XI MAN 1 PONTIANAK - Utari, Dhanty Suci; Wicaksono, Luhur; Purwanti, Purwanti (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
Abstrack If education is only concerned with general knowledge without being given religious knowledge and instilling morals, a generation of people who are smart and knowledgeable but not moral will grow. Therefore, researchers want to find out more about the Relationship of Islamic Education to the Ethics of Students of Class XI MAN 1 Pontianak. The purpose of this study was to find out about the relathionship of Islamic religious education to the ethics of XI MAN 1 Pontianak students. The method used in this research is descriptive method with the form of correlation studies. The results in this study there is a positive correlation between islamic religious education with learner ethics, meaning that the better the islamic religious education he has, the better the ethics of the learner. Data analysis shows that islamic religious education of XI MAN 1 Pontianak students reached 80% in the ?Good? category, while social interaction of XI MAN 1 Pontianak students reached 89% in the ?Good? category.Keywords: Islamic Religious Education, Ethics